Flailing, Hailing, Prevailing: Perceptions of Multi-Robot Failure Recovery Strategies - Reig, Samantha; Carter, Elizabeth J.; Fong, Terrence; Forlizzi, Jodi; Steinfeld, Aaron (2021 16th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2021)
We explored different ways in which a multi-robot system might recover after one robot experiences a failure. We compared four recovery conditions: Update (a robot fixes its error and continues the task), Re-embody (a robot transfers its intelligence to a different body), Call (the failed robot summons a second robot to take its place), and Sense (a second robot detects the failure and proactively takes the place of the first robot). We found that trust in the system and perceived competence of the system were higher when a single robot recovered from a failure on its own (by updating or re-embodying) than when a second robot took over the task. We also found evidence that two robots that used the same socially interactive intelligence were perceived more similarly than two robots with different intelligences. Finally, our study revealed a relationship between how people perceive the agency of a robot and how they perceive the performance of the system. CCS CONCEPTS * Human-centered computing →Laboratory experiments.